Detection of Danger Signs of Acute Respiratory Infections Among Under-Fives & Its Relation to Primary Case Management - Prof. Dr. Ilham Amin Jadoue (International Journal of Medical Sciences And Clinical Research, 2026)
Acute respiratory infections form one of the most important health problems with high morbidity & mortality rate among under-fives, particularly in developing countries. ARIs, diarrhea & malnutrition are considered the main leading killers of children, their importance as a public health problem are of particular significance in developing countries where the associated mortality in children of (U5) is (30–50) times higher than million deaths a year. Children have about (4–6) ARIs episodes each year & make up a large portion of patients seen by health workers at health centers. 90% of which are caused by viruses. (3) In addition to bacteria & fungi Danger signs of ARI are specific symptoms pointed out that ARI episode may be severe or life-threatening requiring immediate medical attention. This is centered around inability of child to drink, difficult breathing & chest indrawing. The objective of this study was focused on early recognition of danger signs & symptoms of ARI episode by mothers & seeking medical attention at proper time, this will show significantly reduce the risk of severe outcomes, including hospitalization & death. The data were obtained via the administration of questionnaires & review of patient chart. The results of this study offer significant contributions to the strategies of primary case management according to severity of ARI episode & ability of mothers to identify danger signs & care seeking behavior.